Quasi Subordination Properties of Bi-Univalent Functions By Using Generalized Srivastava-Attiya Operator - Hameed, Firas N.; Shehab, Nihad H. (Iraqi Journal of Science, 2024)
In this paper, we conduct an investigation into a novel subclass of bi-univalent functions within the unit disk. The introduced subclass incorporates the generalized Srivastava-Attiya operator and satisfies specific quasi-subordination conditions. Through this study, the researchers determine the coefficient estimates  and  for functions within these subclasses and unveil new results by applying the operator to this particular subclass. The implications of these findings extend to complex analysis, number theory, and other branches of mathematics. Overall, this research significantly contributes to the theory of quasi-subordination of bi-univalent functions and enhances the understanding of the diverse applications of the Generalized Srivastava-Attiya Operator.